Neoliberal Colonization in the West Bank. (24th April 2017) - Clarno, Andy
Abstract: In this article, I propose a framework for analyzing context-specific relationships between neoliberal restructuring and simultaneous efforts to reorganize racial and colonial domination. To do so, I explore the articulation between colonization and neoliberalization in the West Bank with a focus on the Bethlehem region. Drawing on qualitative interviews and ethnographic research, the article begins by examining the territorial fragmentation of the Bethlehem region into a series of isolated Palestinian enclosures. These neoliberal enclosures attempt to contain a colonized population that has become increasingly disposable with the restructuring of Israel's economy. As sites of concentrated inequality and intense marginalization, however, they offer only a precarious form of containment. The article then turns to the Palestinian villages, which have become front lines of the struggle over colonization in the West Bank. In the hills west of Bethlehem, Palestinian villagers confront colonial violence by Israeli settlers and the state. They also confront a crisis of unemployment and rapid urbanization due to neoliberal restructuring. These dynamics have combined to create an indirect form of displacement and a market-based strategy of colonization. Overall, therefore, Palestinians in the West Bank today confront a unique form of neoliberal colonization .